The practicability of the acceptance in Iloilo City of skin care products and processes that hinder aging in women - Mesia, Felinwright; Regencia, Donnabelle May.; Sazon, Vivien Grace; Taytayon, Cherie; Vencer, Katherine Mae. (2003)
The primary objective of the study was to evaluate the practicability of the acceptance in Iloilo City of skin care products and processes that hinder aging in women. In attaining the objective, the researchers employed varied sampling and data gathering techniques; and subjected the data to frequency analysis to determine the different factors and their respective contribution to the acceptance of skin care product and processes. The study revealed that women within the age bracket of twenty to sixty, regardless of their placement in the age range, were more than ready to avail of skin care products and processes. Their willingness were greatly motivated by different factor's whose influence vary significantly. socially orientation was the most prevailing factor followed by vanity, age, culture, economic status and civil status. willingness on the other hand was primarily restrained by the person's capability to generate cash to compensate for availing skin care products and services. Other factors, which usually intervene with the desire of the person, were also given such as his busy schedule, indifference and contentment.
[Research Paper] (BA 200 - Business Research) -- [Iloilo City : UPV-CM], March 17, 2003.